Olimpíadas de Física e o ensino de Física experimental - Lima, Leonardo Bruno Pedroza Pontes (2017)
The Scientific Olympiad is a tool used in many countries of the world to optimize teaching / learning processes and to encourage high school students, or equivalent, to pursue technological careers. In Brazil, the Brazilian Physics Olympiad (OBF) is an important program maintained by the Brazilian Society of Physics that aims to contribute to the development of Physics teaching. One of the main objectives of the OBF is to prepare students to compete in International Physics Olympiads. These competitions are important because they provide a benchmark for assessing the world-wide physics teaching we are practicing. However, there is a lack in the available literature of works that do this evaluation at world level. Thus, in this work, first, an analysis was made of the success of the OBF in the preparation of students through the results obtained in the International Physics Olympiad (IPhO). Positive and negative points were investigated, aiming to construct an educational product that contributes to the improvement of the program. We analyzed the performance of Brazil in the editions in which it participated and verified whether there was evolution in the overall performance. Then, we analyze the performance separately in the Theoretical and Experimental tests, comparing with the overall performance. We also analyzed the results in a school's OBF 2016 and compared it with the overall results of all participants. The analysis indicated that the contribution should be made in the teaching of Experimental Physics. Finally, as an final product of this work, an experimental physics booklet was developed for teachers and high school students. The handout addresses the concepts of experimental physics in a language appropriate to high school students and teachers.